Intraguild predation between lady beetles and lacewings: outcomes and consequences vary with focal prey and arena of interaction - Noppe, Christophe; Michaud, J. P.; De Clercq, Patrick (My University, 2012)
We examined reciprocal intraguild predation (IGP) and cannibalism among various combinations of Coleomegilla maculata DeGeer and Chrysoperla carnea Stephens larvae as they developed feeding on greenbugs, Schizaphis graminum Rondani, on sorghum plants in microcosms. Pairs of C. maculata larvae suppressed aphids better than pairs of C. carnea larvae or heterospecific larval pairs and yielded the highest rate of plant survival. IGP by C. carnea larvae occurred mostly in the first instar, whereas C. maculata larvae were more aggressive in later instars. Although C. carnea was the superior intraguild predator, winning 62.7% of contests in microcosms, this value increased to 88.9% when the experiment was repeated in petri dishes without plant material, regardless of whether greenbugs or eggs of Ephestia kuehniella Zeller were offered as focal prey. Provision in petri dishes of the sessile, higher quality prey (Ephestia) as opposed to greenbugs, improved the survival of solitary larvae and delayed cannibalism and IGP until later developmental stages in both species. Larvae of C. maculata that cannibalized took longer to develop and weighed less at pupation, independent of the arena or prey offered. Although larvae of C. carnea did not pay a cost for cannibalism or IGP in microcosms, there were some negative developmental effects of IGP in petri dishes, particularly on the Ephestia diet. These results illustrate how the plant, as a substrate, can mediate the strength of IGP interactions and how the relative suitability of the focal prey can influence both the timing and consequences of cannibalism and IGP.
Citation: Noppe, Christophe, J. P. Michaud, and Patrick De Clercq. 2012. “Intraguild Predation Between Lady Beetles and Lacewings: Outcomes and Consequences Vary With Focal Prey and Arena of Interaction.” Annals of the Entomological Society of America 105 (4): 562–71. https://doi.org/10.1603/AN11165.
Keywords: Cannibalism; Coccinellidae; Chrysopidae; Ephestia kuehniella; Schizaphis graminum